2000
DOI: 10.1016/s0378-1097(00)00482-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of secreted proteins of the cyanobacterium Synechocystis sp. strain PCC 6803

Abstract: We investigated the spectrum of secreted proteins in the cyanobacterium Synechocystis, and identified these proteins by amino-terminal sequencing. In total, seven sequences have been determined that corresponded to the proteins Sll0044, Sll1694, Sll1891, Slr0924, Slr0841, Slr0168, and Slr1855. The protein Sll1694 of 18 kDa that formed one of two major bands on SDS^PAGE was identified as cyanobacterial pilin, PilA. The amino-terminal sequence of another protein that formed a second major band was blocked. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…In the previous study we identified PilA1 as the major secreted protein of Synechocystis [15]. The deduced amino acid sequence of the leader peptide of PilA1 (Sll1694) was used in this study to elucidate its actual ability to secrete proteins into culture medium.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the previous study we identified PilA1 as the major secreted protein of Synechocystis [15]. The deduced amino acid sequence of the leader peptide of PilA1 (Sll1694) was used in this study to elucidate its actual ability to secrete proteins into culture medium.…”
Section: Discussionmentioning
confidence: 99%
“…The supernatant was re‐centrifuged and filtered through a Stericap filter unit. Isolation of secreted proteins from the culture medium was performed as described earlier[15]. Proteins were separated by electrophoresis in 12% SDS–PAGE and in parallel, in 12% SDS–PAGE that contained 0.2% of lichenan.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several cyanobacteria produce extracellular metabolites, such as polypeptides (Sergeyenko and Los 2000) and polysaccharides (De Philippis and Vincenzini 1998;Otero and Vincenzini 2003). Our results show that, Oscillatoria sp.…”
Section: Discussionmentioning
confidence: 62%